Study of Fauna Diversity in Ujung Kulon National Park Banten Indonesia - Suroso Mukti Leksono; Septi kurniasih; Pipit Marianingsih; Adi Nestiadi (Universitas Tidar, 2023)
National parks are natural conservation areas that have native ecosystems, managed with a zoning system that is used for research, science, education, tourism, cultivation and recreation purposes. Ujung Kulon National Park (TNUK) is one of Indonesia's national parks, located on the western tip of Java Island, Pandeglang Regency, Banten Province. The various kinds of ecosystems in Ujung Kulon National Park are a habitat for various endemic animals or those with a protected and endangered conservation status. However, climate change and poaching that have occurred over the years, land transfers, and climate change have created distinct threats to the preservation of fauna in this region. One of the efforts to preserve the environment in and around TNUK is to carry out in-depth research on habitat conditions and the diversity of species present inside the area. This research aims to obtain information on the diversity of fauna in the TNUK and identify the various types of fauna found in the TNUK area. Fauna's diversity information was carried out in September 2022 by exploring areas in Cilintang to Legon Pakis with a total distance of 9.7 km. The study found the diversity of fauna, and there are nine species of large mammals, seven species of herpetofauna (amphibian reptiles), 13 species of butterflies, and 30 species of avifauna (aves).